2013
DOI: 10.3109/01443615.2012.758089
|View full text |Cite
|
Sign up to set email alerts
|

Platelet volume as a parameter for platelet activation in patients with endometrial cancer

Abstract: The objective of this study was to use mean platelet volume (MPV) as a measure of platelet activation in patients with endometrial adenocarcinoma and healthy controls. There was a total of 310 patients with endometrial adenocarcinoma retrospectively evaluated and 250 healthy controls. Preoperative haemoglobin, platelet counts and mean platelet volume were evaluated and statistical tests were conducted to determine the differences among early and advanced disease groups and controls. Median haemoglobin (13.0 vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 19 publications
2
44
1
Order By: Relevance
“…Previous studies have demonstrated that the MPV was higher in patients with gastric cancer than in control patients and also MPV/ PC (platelet count) ratio was significantly increased in the hepatocellular carcinoma patients (Cho et al, 2013;Kilincalp et al, 2013). In addition, Oge et al (2013) showed that MPV was significantly higher in endometrial cancer patients than the control group. Our data showed statistically significant differences in MPV values between mCRC and non-mCRC, this may be explained with the increased inflammation and increased platelet activation in the metastatic disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have demonstrated that the MPV was higher in patients with gastric cancer than in control patients and also MPV/ PC (platelet count) ratio was significantly increased in the hepatocellular carcinoma patients (Cho et al, 2013;Kilincalp et al, 2013). In addition, Oge et al (2013) showed that MPV was significantly higher in endometrial cancer patients than the control group. Our data showed statistically significant differences in MPV values between mCRC and non-mCRC, this may be explained with the increased inflammation and increased platelet activation in the metastatic disease.…”
Section: Discussionmentioning
confidence: 96%
“…Platelets play important role in pathophysiology of tumor angiogenesis by transporting VEGF, which is the target for anti-angiogenic agents (Oge et al, 2013). MPV is a parameter of platelet size and can reflect changes in the rate of platelet production.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 This situation with different cytokines that have proinflammatory characteristics is very important for cancer patients. [18][19][20][21][22][23][24][25] However, Osada et al 18 reported that increased MPV level was very important in stomach cancer patients in compared with healthy subjects. 10,[12][13][14][15] Some studies did not find a relationship between MPV and platelet count as a prognostic factors in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…MPV is an indicator of the average thrombocyte volume, recognized as a hallmark of platelet production rate and stimulation. The association between increased MPV and the presence of many solid tumors such as hepatocellular carcinoma, pancreatic carcinoma, lung cancer, endometrial cancer, and gastric cancer has been widely reported (Karaman et al, 2011;Kurt et al, 2012;Ishizuka et al, 2013;Kılınçalp et al, 2013;Oge et al, 2013;Inagaki et al, 2014). However, the predictive value or usefulness of NLR, PLR, and MPV in the diagnosis and follow-up of CRC has not been investigated yet.…”
Section: Introductionmentioning
confidence: 91%